Peningkatan Kapasitas Masyarakat dalam Pengelolaan Desa Wisata Sangurejo - Dhimas Setyo Nugroho (Sekolah Tinggi Pariwisata AMPTA Yogyakarta, 2023)
This Community Service Activity (PKM) aims to increase the capacity of the Sangurejo tourism village community in managing the tourism village. This PKM activity includes socialization of the digitalization of marketing village tourism branding, tourism awareness socialization, and socialization of Sapta Pesona. Through the dissemination of digitalization of tourism village marketing branding, the community and tourism actors in the Sangurejo Tourism Village gain a better understanding of the importance of utilizing technology and digital media in promoting tourist destinations. Tourism awareness dissemination provides an understanding of the importance of maintaining tourism sustainability, cultural preservation, and responsible tourism management. Meanwhile, the socialization of Sapta Pesona enriches the understanding of the attractiveness of tourism and the potential of tourist villages.